(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The nervous system, on the one hand, adapts to the metabolic and physiological processes that pass to various tissues, organs and systems, and on the other hand, with its help, performs the function of maintaining the connection between the whole organism and the external environment. During ontogeny, various parts of the nervous system merge into a functional system, mature and harmonize with age. This article provides information about the general features of the nervous system and higher nervous activity in children.